Evaluation of the Use of Superconducting 380 kV Cable - Kottonau, Dustin (Karlsruher Schriftenreihe zur Supraleitung, 2020)
This study describes the design of superconducting cables for use in the 380 kV three-phase network and explains general aspects of the use of such cables in the extra-high voltage grid. It compares the superconducting technology with other line technologies under many different criteria.